Gold Nanoparticles as X-Ray, CT, and Multimodal Imaging Contrast Agents: Formulation, Targeting, and Methodology. (7th March 2018) - Mahan, Matthew M.; Doiron, Amber L.
Abstract : Computed tomography (CT) is among the most popular medical imaging modalities due to its high resolution images, fast scan time, low cost, and compatibility with all patients. CT scans of soft tissues require the localization of imaging contrast agents (CA) to create contrast, revealing anatomic information. Gold nanoparticles (AuNP) have attracted interest recently for their use as CT CA due to their high X-ray attenuation, simple surface chemistry, and biocompatibility. Targeting molecules may be attached to the particles to allow for the targeting of specific cell types and disease states. AuNP can also be readily designed to incorporate other imaging contrast agents such as rare earth metals and dyes. This review summarizes the current state-of-the-art knowledge in the field of AuNP used as X-ray and multimodal contrast agents. Primary research is analyzed through the lens of structure-property-function to best explain the design of a particle for a given application. Design specification of particles includes size, shape, surface functionalization, composition, circulation time, and component synergy. Key considerations include delivery of a CA payload to the site of interest, nontoxicity of particle components, and contrast enhancement compared to the surrounding tissue. Examples from literature are included to illustrate the strategies used to address design considerations.